2002
DOI: 10.1097/00005392-200206000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Mineral Density, Lean Body Mass and Fat Content as Measured by Dual Energy X-Ray Absorptiometry in Patients With Prostate Cancer Without Apparent Bone Metastases Given Androgen Deprivation Therapy

Abstract: Serial bone densitometry evaluation during androgen deprivation therapy may allow the detection of patients with prostate cancer at risk for osteoporotic fractures, that is those with osteopenia or osteoporosis at baseline and fast bone loss. The change in body composition may predispose patients to accidental falls, thus increasing the risk of bone fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 21 publications
5
98
0
1
Order By: Relevance
“…Sleep disorders were only marginally affected, whereas no effect on anxiety was observed. Since depression, quality of life and, to a lesser extent, self body image perception were reciprocally correlated, an interesting issue is whether the depressive symptoms in our series were associated directly with testosterone deficiency or indirectly as a consequence of fatigue, physical impairment, and changes in body image related to ADT [34,35]. A multivariate logistic regression analysis showed that depression was independently associated with ADT and this suggests a direct effect of treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Sleep disorders were only marginally affected, whereas no effect on anxiety was observed. Since depression, quality of life and, to a lesser extent, self body image perception were reciprocally correlated, an interesting issue is whether the depressive symptoms in our series were associated directly with testosterone deficiency or indirectly as a consequence of fatigue, physical impairment, and changes in body image related to ADT [34,35]. A multivariate logistic regression analysis showed that depression was independently associated with ADT and this suggests a direct effect of treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Recent cross-sectional data have demonstrate that men with prostate carcinoma who receive ADT, on average, have BMD measurements that are 6.5-17.3% lower compared with BMD measurements in eugonadal men who are treated without androgen blockade. 5,6,10,14,18 The duration of ADT affects BMD values significantly. Kiratli et al, for example, reported spinal BMD values of 14% less and hip BMD values of 28% less than the values observed in age-matched control individuals after 10 years of ADT, compared with spinal BMD values of 1.7% less and hip BMD values of 5.2% less than the values observed in age-matched controls after only 2 years of ADT.…”
Section: Bmd Changes In Normal Men and In Men With Prostate Carcinomamentioning
confidence: 99%
“…GnRH agonist significantly decrease lean body mass and increase fat mass in men with prostate cancer [27,[63][64][65][66]. In two prospective studies of men with nonmetastatic prostate cancer, for example, we demonstrated that GnRH agonists decreased lean body mass by 2.7 to 3.8% and increase fat mass by 9.4 to 11.0% from baseline to 1 year [65,66].…”
Section: Treatment-related Changes In Body Compositionmentioning
confidence: 60%
“…GnRH agonists significantly decrease bone mineral density in men with prostate cancer [23][24][25][26][27][28]. Most studies report 2-3% decrease per year in bone mineral density of the hip and spine during initial therapy.…”
Section: Changes In Bone Mineral Density During Androgen Deprivation mentioning
confidence: 99%